2013
DOI: 10.1002/jgrd.50384
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and production of reactive mercury and dissolved gaseous mercury in surface waters and water/air mercury flux in reservoirs on Wujiang River, Southwest China

Abstract: [1] Transformation and distribution of mercury (Hg) species play an important role in the biogeochemical cycling of mercury in aquatic systems. Measurements of water/air exchange fluxes of Hg, reactive mercury (RHg), and dissolved gaseous mercury (DGM) concentrations were conducted at 14 sites in five reservoirs on the Wujiang River, Guizhou, Southwest China. Clear spatial and temporal variations in Hg fluxes, RHg, and DGM concentrations were observed in the study area. Hg fluxes and RHg concentrations exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 48 publications
4
5
0
Order By: Relevance
“…Generally, the gaseous Hg fluxes at the WAI were significantly higher in summer (p < 0.05, Dunn's test) than autumn and spring at all sites (Figure 3). The highest values of gaseous Hg fluxes found in summer are related to the intensity of the incident solar radiation, as observed in several studies conducted in both marine (e.g., [67,68,105]) and freshwater environments (e.g., [19,98,99]); in fact, solar radiation is a key factor in promoting a faster rate of DGM production in warmer periods via the photoreduction of Hg 2+ in surface waters and the subsequent evasion to the atmosphere The highest values of gaseous Hg fluxes found in summer are related to the intensity of the incident solar radiation, as observed in several studies conducted in both marine (e.g., [67,68,105]) and freshwater environments (e.g., [19,98,99]); in fact, solar radiation is a key factor in promoting a faster rate of DGM production in warmer periods via the photoreduction of Hg 2+ in surface waters and the subsequent evasion to the atmosphere [26,[106][107][108]. This was also confirmed in this study, as high DGM concentrations were detected in summer and the lowest in autumn in parallel with UV radiation intensity, which is most effective in systems with low DOC content that in turn allow for higher light penetration [24,26].…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…Generally, the gaseous Hg fluxes at the WAI were significantly higher in summer (p < 0.05, Dunn's test) than autumn and spring at all sites (Figure 3). The highest values of gaseous Hg fluxes found in summer are related to the intensity of the incident solar radiation, as observed in several studies conducted in both marine (e.g., [67,68,105]) and freshwater environments (e.g., [19,98,99]); in fact, solar radiation is a key factor in promoting a faster rate of DGM production in warmer periods via the photoreduction of Hg 2+ in surface waters and the subsequent evasion to the atmosphere The highest values of gaseous Hg fluxes found in summer are related to the intensity of the incident solar radiation, as observed in several studies conducted in both marine (e.g., [67,68,105]) and freshwater environments (e.g., [19,98,99]); in fact, solar radiation is a key factor in promoting a faster rate of DGM production in warmer periods via the photoreduction of Hg 2+ in surface waters and the subsequent evasion to the atmosphere [26,[106][107][108]. This was also confirmed in this study, as high DGM concentrations were detected in summer and the lowest in autumn in parallel with UV radiation intensity, which is most effective in systems with low DOC content that in turn allow for higher light penetration [24,26].…”
Section: Discussionsupporting
confidence: 58%
“…This value is in agreement with those usually reported for lake water ( [35] and references therein). The highest values of gaseous Hg fluxes found in summer are related to the intensity of the incident solar radiation, as observed in several studies conducted in both marine (e.g., [67,68,105]) and freshwater environments (e.g., [19,98,99]); in fact, solar radiation is a key factor in promoting a faster rate of DGM production in warmer periods via the photoreduction of Hg 2+ in surface waters and the subsequent evasion to the atmosphere [26,[106][107][108]. This was also confirmed in this study, as high DGM concentrations were detected in summer and the lowest in autumn in parallel with UV radiation intensity, which is most effective in systems with low DOC content that in turn allow for higher light penetration [24,26].…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…GEM fluxes from different landscapes in cold seasons (from November to April) were relatively limited. Several studies found that GEM Fu et al (2007Fu et al ( , 2008Fu et al ( , 2010bFu et al ( , 2012cFu et al ( , 2013, Zhu et al (2011Zhu et al ( , 2013, Ma et al (2013), and Liu et al (2014) fluxes from dry farmland, forest soil, and lake waters were about 2.5-40 times (mean = 6.5, n = 18) lower than those in warm seasons Ma et al, 2013;Fu et al, 2010b;Fu et al, 2013). Given the different landscapes and seasonal patterns of GEM fluxes in mainland China, we estimate the annual natural GEM emissions to be 528 t in China.…”
Section: Estimates Of Gem Emissionsmentioning
confidence: 97%